Microsoft Office step by step (Office 2021 and Microsoft 365) - Lambert, Joan (Step by step (Redmond, Wash.), 2022)
The quick way to learn popular Microsoft 365 apps! This is learning made easy. Get more done quickly with Microsoft Word, Excel, PowerPoint, and Outlook. Jump in wherever you need answersbrisk lessons and detailed screenshots show you exactly what to do, step by step. Discover new time-savers and usability improvements for Word, Excel, PowerPoint, and Outlook Format and organize high-impact documents and use Words enhanced coauthoring tools Build powerful, reliable Excel worksheets and analyze complex data sets Prepare highly effective presentations with PowerPoints newest visual tools Improve your productivity with Outlook email, scheduling, and contacts Make the most of the latest Accessibility Checker and other new features Look up just the tasks and lessons you need Download your Step by Step practice files at: MicrosoftPressStore.com/MSOfficeSBS365/downloads.